In Vitro Microbiological and Drug Release of Silver/Ibuprofen Loaded Wound Dressing Designed for the Treatment of Chronically Infected Painful Wounds - Alejandra Mogrovejo-Valdivia; Mickael Maton; Maria Jose Garcia-Fernandez; Nicolas Tabary; Feng Chai; Christel Neut; Bernard Martel; Nicolas Blanchemain (MDPI AG, 2021)
This study consisted of developing a dressing loaded with silver (Ag) and ibuprofen (IBU) that provides a dual therapy, antibacterial and antalgic, intended for infected painful wounds. Therefore, non-woven polyethyleneterephtalate (PET) textiles nonwovens were pre-treated by cyclodextrin crosslinked with citric acid by a pad/dry/cure process. Then, textiles were impregnated in silver solution followed by a thermal treatment and were then coated by Layer-by-Layer (L-b-L) deposition of a polyelectrolyte multilayer (PEM) system consisting of anionic water-soluble poly(betacyclodextrin citrate) (PCD) and cationic chitosan. Finally, ibuprofen lysinate (IBU-L) was loaded on the PEM coating. We demonstrated the complexation of IBU with native βCD and PCD by phase solubility diagram and 1H NMR. PEM system allowed complete IBU-L release in 6 h in PBS pH 7.4 batch (USP IV). On the other hand, microbiological tests demonstrated that loaded silver induced bacterial reduction of 4 Log10 against S. aureus and E. coli and tests revealed that ibuprofen lysinate loading did not interfere with the antibacterial properties of the dressing.